Nonequilibrium distribution functions of nucleons in relativistic nucleus-nucleus collisions - Anchishkin, D.; Naboka, V.; Cleymans, J. (Condensed Matter Physics, 2013)
The collision smearing of the nucleon momenta about their initial values during relativistic nucleus-nucleus collisions is investigated. To a certain degree, our model belongs to the transport type, and we investigate the evolution of the nucleon system created at a nucleus-nucleus collision. However, we parameterize this development by the number of collisions of every particle during evolution rather than by the time variable. It is assumed that the group of nucleons which leave the system after the same number of collisions can be joined in a particular statistical ensemble. The nucleon nonequilibrium distribution functions are derived which depend on a certain number of collisions of a nucleon before a freeze-out. Дослiджується розмиття iмпульсiв нуклонiв навколо своїх початкових значень, яке вiдбувається в релятивiстичних ядро-ядерних зiткненнях. Наша модель вiдноситься, певною мiрою, до транспортних, ми до-слiдили еволюцiю нуклонної системи, створеної в ядро-ядерних зiткненнях, але ми параметризуємо цей розвиток не часом, а числом зiткнень кожної частинки. Припускається, що група нуклонiв, якi залишають систему зазнавши однакову кiлькiсть зiткнень, можуть бути об’єднанi в певний статистичний ансамбль. Обраховується нерiвноважна функцiя розподiлу нуклонiв в iмпульсному просторi, яка залежить вiд певного числа зiткнень нуклона перед випромiнюванням iз системи.